Assessment of Nurses’ Knowledge toward Infection Control Measures for Hepatitis 8 Virus in Hemodialysis Units - Serwan J. Bakey (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: to assess nurses’ knowledge toward infection control measures for hepatitis a virus in hemodialysis units and to detemine the relationship between nurses’ knowledge and their demographical characteristics. %eihs:::°mg:rA5th:e;:#tt£:eoscTodbyerw9¥,C22;5];e.d°utathem°dialysisunitsofBaghdadTeachingHospha|sstated A non-probability `tturposive" sample of (51) nurses, who were working in hemodialysis units were selected from Baghdad teaching hosphals. The data were collected through the use of constructed questionnaire, which consists of two parts (I) Demographic data fom that consists of 10 items and (2) Nurses’ knowledge form that consists of 6 sections contain 79 items, by means of direct interview technique with the nurses. The validity of #eo:u£Stla°#]:Tes#:t:)¥mwe:T:¥dp:::e#::gtitoth(e];)e:Poedc]:I:Sieipper¥La,n4dth:ts2:eo):abufi]t¥%aasyd:tthe,¥omoe8d Descriptive statistical analysis procedures (frequency, percentage, mean of score) and inferential statistical analysis procedures (person correlation coefficient, contingency coefficient) were used for the data analysis. Results: The findings of the study indicated that there is a knowledge deficit of nurses in some aspects relative to infection control measures. No sigrificant relationship was found between nurses’ knowledge and their gender, marital status and years of experience in hospital, while a significant relationship was found between nurses’ knowledge and their age, level of education, years of experience in hemodialysis unit, sharing in training sessions and duration of training session that the nurses were engaged in it.